Analisis Efek Penggunaan Gawai Terhadap Remaja Dalam Perspektif Teori Depedensi dan Islam - Ramadan; Fakhri Yusuf (Sadida Islamic Communications and Media Studies, 2024)
This research discusses the analysis of the effects of cellphone media on the behavior of teenagers from the perspective of dependency theory and its relationship to Islam. Mobile phones have become an integral part of everyday life, especially among teenagers. However, excessive use of cellphones can have a negative impact on teenagers' behavior, such as being busy and focused on playing online games, disrupting moral development, and reducing social interaction. From the perspective of dependency theory, this research shows that the use of cellphones can make teenagers dependent on technology and neglect other obligations, such as studying for school, neglecting prayer times and minimal social interaction. In this research the author uses qualitative research methods, Qualitative Research is research that is used to investigate, discover, describe, or explain the situation of social influences that cannot be explained, measured or described using a quantitative approach, this research approach starts from data, utilizing theories that exists as explanatory material and ends up being a theory.